Structure and tree species composition of forest fringe of a forest fragment in an oil palm plantation at Suai, Sarawak, Malaysian Borneo - Claudia Lennya Jana; ISMAIL JUSOH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Jana CL, Jusoh I. 2021. Structure and Tree Species Composition of Forest Fringe of A Forest Fragment in an Oil Palm Plantation at Suai, Sarawak, Malaysian Borne. Biodiversitas 22: 3013-3019. Forest fragments in oil palm plantations are remnants of the original forest tract with various sizes and shapes after clearing forested lands for crops and roads. Fragmented forests usually created forest fringe or edge habitats that differ in light intensity, temperature, humidity, heavy rainfall, and strong winds from its core. The study was aimed to determine the structure and tree species composition of the forest fringe of a fragmented forest in an oil palm plantation Suai, Sarawak. This study established a total of 24 sampling plots within the forest fringe. Tree enumeration and species identification were conducted in all sampling plots to all trees with a diameter at breast height 5 cm and higher.  A total of 59 families comprised of 274 species and 948 trees individuals were recorded. The aboveground biomass stand at 260 Mg ha?¹. Species Elateriospermum tapos was predominant, and family Dipterocarpaceace dominated the forest fringe.   Based on the calculated indices, species diversity and richness were considered high, while the dispersion of individual trees was random but unevenly distributed. Natural regeneration in the forest fringe is sustainable. The forest structure and species composition are intact, and without significant disturbance, the whole forest fragment is self-sustain.